DESAIN SHOW ROOM BAGI PARA PERAJIN ROTAN DS. TRANGSAN, KEC. GATAK, KAB. SUKOHARJO - Sumarno Sumarno; Indarto Indarto (Pendhapa, 2018)
ABSTRACTThe purpose of this study is to realize the building of a product show room in the center of the Trangsan rattan handicraft industry, Gatak, Sukoharjo through cooperation between various elements. The existence of a show room is to facilitate prospective tourists in looking for rattan handicraft products and increasing the sales of rattan crafters is the purpose of this study. The method used to achieve these results is by planning, designing, building and displaying products in the show room. The collaboration between various parties involved, therefore researchers are more focused on the activities of planning, designing, and monitoring development. The planned location of the construction of the show room is in the Trangsan Village Hall complex. The process of designing data sources is obtained through existing conditions, literature, and informants. Data collection techniques are through interviews, literature review, documentation and Forum Group Discution (FGD). Data analysis is through interactive analysis which includes three components which include data reduction, data presentation (data display) and data validation (verification). The results of the study are in the form of design drawings which include work drawings, perspectives and detailed drawings ... Keywords: displays, products, rattanÂ